The role of SAP in corporate finance division of Edotco Bangladesh Co Ltd - Khan, Alif-Uz-Zaman (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.